Pengaruh Perbandingan Minyak dan Surfaktan serta Suhu terhadap Karakteristik Sediaan Krim - Hendrawan, I Made Mas Oka; Suhendra, Lutfi; Ganda Putra, G.P. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
This study aims to determine the effect of oil and surfactant comparisons and the temperature to the resultant dosage characteristics and determine the oil and surfactant ratio and the appropriate temperature for the preparation of cream. This study uses the group random two-factor design. The first factor is the comparison of oil that is mixture of cocoa fat and virgin coconut oil with surfactants that is mixture of tween 80 and span 80 consisting of 3 levels, which are 85% ; 15%, 80% ; 20% and 85% ; 25%. The second factor is temperature consisting of 3 levels, which are 60 º C, 70 º C and 80 º C. Results of this study showed the treatment of oil comparison and surfactants were had an strongly effect to the homogeneity, adhesive time, spread ability, separation ratio and viscosity, but had no effect on the pH of cream preparations. Temperature treatment had an strongly effect on homogeneity, adhesive time, spread ability, separation ratio and viscosity, while only had an effect on the pH of a basic cream. Interaction between the treatment had an effect on the ratio of separation, pH as well as the spread of cream preparations, but no had effect on adhesive time and the viscosity of the preparation of cream. Oil comparison and surfactant treatment of 80%: 20% and temperature 70ºC is the best treatment resulting in a cream preparations with homogenity characteristics, adhesive time 7.14 Second, ratio of separator 0.48, spread ability of 6.83 cm, viscosity of 37000 cps and pH 6.05. Keywords: oil, surfactans, temperature, cocoa fats, virgin coconut oil, tween 80 and span 80